High-temperature service life tests of full-size thermosyphons - Balunov Boris; Egorov Mikle (E3S Web of Conferences, 2019)
During past two decades, at temperature 240-265°C, resource tests were carried out on 19 thermosyphons of full-scale sizes: 45х4 mm in diameter, 4.92 m in length. The thermosyphons were prepared with varying preliminary surface treatment methods, composition of the aqueous solution to be poured into the thermosyphons, location of titanium chips in the perforated capsules under the lid of the thermosyphons. With a period of 1 to 3 years, thermosyphons were removed from testing system for 30 hours to control the vacuum by thermal method that does not require depressurization. At the last control experiment, four thermosyphons are depressurized for the following purposes: to check the condition of their internal surface in different zones along the length; for the chemical analysis of the aqueous solution poured from them; to determine the structure and characteristics of the mechanical properties of the thermosyphon metal. The main aim of the tests is to justify maintaining the structure and mechanical properties of the metal for a long time, keeping a vacuum of 90-95% inside the thermosyphon, ensuring high heat transfer characteristics of the boiling operating mode of thermosyphons.